Correlation of arterial PaCO2 to end tidal CO2 in children undergoing laparoscopic abdominal surgery: An observational study - S Jain; L Kumar; S C Babu; A Sadhoo; G C Ravindran; S Rajan (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: The reliability of end tidal carbon dioxide (ETCO2) as a measure of arterial carbon dioxide (PaCO2) in pediatric laparoscopy is unclear. We evaluated the correlation of arterial to end tidal P(a-ET) CO2 during pediatric laparoscopy at two hours of pneumoperitoneum as the primary objective. We also compared P(a-ET) CO2 and alveolar to arterial oxygen gradient P(A-a) O2 and haemodynamics at fixed time points during surgery. Material and Methods: A cross-sectional study was conducted in 25 children undergoing laparoscopic abdominal surgery. Arterial blood gases were drawn at T0, baseline, T10: ten minutes, T1h: 1 hour, T2h: 2 hours of pnuemoperitoneum and T 10d: 10 mins after deflation. The P(a-ET) CO2, P(A-a) O2, were measured from the blood gas and ETCO2 and FiO2 values on the monitor. The Pearson's correlation coefficient, the Wilcoxon rank test and Chi square test were used for statistical analysis. Results: At T2h moderate correlation of P(a-ET) CO2 (r = 0.605, P = 0.001) with 40% children documenting accurate P(a-ET) CO2, -1 to +1 mm Hg was seen. Moderate correlation was also seen at T0, T10, T 10d but poor correlation at T 1h. The P(A-a) O2 increased progressively with surgery and did not correlate with P(a-ET) CO2. Heart rate was stable, but systolic blood pressures at T 10 and diastolic at T10, T 1h, T 2h were higher than baseline. Conclusion: Moderate correlation was seen between PaCO2 and ETCO2 at 2 h of pnuemoperitoneum and at T0, T 10, and T 10d. P(A-a) O2 increased with surgery but did not correlate with P(a-ET) CO2.